Meningkatkan Kepuasan Pelanggan Melalui Peran Mediasi Kepercayaan Studi Kasus di Sleepless Owls Coffee Tebet - Ulfa Dwi Lestari; Parlagutan Silitonga (Panorama Nusantara, 2022)
This study aims to analyze the effect of product quality and service quality on customer satisfaction through mediation of trust in Sleepless Owls Coffee Tebet. The respondents included in the study were Sleepless Owls Coffee customers who had come at least 2 times and bought food products. Purposive sampling is an option in sampling with a total of 150 respondents. This study uses a quantitative analysis method through path analysis with SmartPLS 3.0. Based on the results of the path coefficient analysis test, there is a significant effect of product quality and service quality on customer satisfaction. Significant influence of product quality and service quality on trust. The significant effect of trust on customer satisfaction and the existence of a significant indirect effect between product quality and service quality on customer satisfaction through trust mediation.